Numerical analysis of transcritical carbon dioxide compression cycle: a case study - keshtkar, Mohammad Mehdi (Journal of Advanced Computer Science & Technology, 2018)
This study deals with thermodynamic investigation of a refrigeration compression cycle with carbon dioxide refrigerant and two stage compression. In this paper, the effect of intercooler in the two-stage compression system at different pressures of gas cooler is investigated. In addition, the performance of one stage compression cycle and two-stage compression cycle are compared and eventually, the performance of system is investigated under the influence of the change of variables such as gas coolerÂ  pressure, isentropic efficiency of the compressors, the intercooling rate between the two stages of compression, the refrigerant gas cooler outlet temperature is examined. Due to evaporation temperature in the evaporator Â and refrigeration capacity (kW) results show that the coefficient of performance in the two-stage compression with intercooler is increased compared to the single-stage compression cycle.